Reflection on the proposed changes to dose quantities—an industrial perspective. (6th December 2021) - Lips, M; Anderson, E; Nishida, K; Schneider, G; Zic, J; Sanders, C; Owen, J; Hondros, J; de Ruvo, A
Abstract: In 2021, the ICRP initiated the revision of the general recommendations of the system of radiation protection, and part of it will focus on dose quantities. The recently published ICRP Publication 147 and ICRU Report 95 have described the extent of the proposed modifications and paved the way for the strategy to be adopted. These revisions would seek to simplify, improve the accuracy and extend the field of use of dose quantities. While the Radiological Protection Working Group of the World Nuclear Association recognises the notable improvement in the estimation of the protection quantities and the usefulness of such changes for the medical and research sector, the benefits of the proposed new system seem very limited for the nuclear industry and industries involving naturally occurring radioactive materials. The complexity associated with changing a long-standing and robust system and the risk incurred by the human factor seem unjustified, bearing in mind the likely cost.